SYNTHESIS AND CHARACTERIZATION OF NANOPARTICLES OF ZINC PEROXIDE (ZnO2) OBTAINED BY SOL-GEL TECHNIQUE - Colonia S., R. (2010)
Nanoparticles of zinc peroxide were synthesized by sol-gel technique using as precursors aqueous solutions of zinc acetate di-hydrate (Zn(CH3COO)2.2H2O) and hydrogen peroxide (H2O2) at 30%. During the synthesis the sol was exposed to an specific radiation (gamma or ultraviolet). The structure of the ZnO2 nanoparticles was characterized by X-ray diffraction. The sol absorbance vs. the time of irradiation was studied for UV irradiated sols. Thin films of ZnO2-ZnO were made using spray pyrolysis of the irradiated sols. The morphology of these films was studied by atomic force microscopy.